ANALISIS MINYAK KAYU PUTIH (Melaleuca cajuputi Powell) ASAL PULAU FLORES - Sawu, Maria S. M.; Nitbani, Febri O.; Ishaq Lerrick, Reinner (Chemistry Notes, 2023)
Analysis of essential oil contained in Flores’s Melaleuca cajuputi Powell leaves has been done over GC-MS spectrometer. By distilling of the pre-dried leave samples using Stahl apparatus, there was 3% of colorless and cajuputi typical oil yielded. The GC-MS detected 16 compounds mainly 63% of 1,8-cineol, 11% of α-terpineol, and 12% -terpenylacetate.